Mobile recommender system based on smart city graph - Khalid Khoshnaw, Karwan Hoshyar; Abdulkarim Shwany, Zardasht Abdulaziz; Mustafa, Twana; Ismail, Shayda Khudhur (Institute of Advanced Engineering and Science, 2022)
Mobile recommender systems have changed the way people find items, purposes of intrigue, administrations, or even new companions. The innovation behind mobile recommender systems has developed to give client inclinations and social impacts. This paper introduces a first way to build a mobile recommendation system based on smart city graphs that appear topic features, user profiles, and impacts acquired from social connections. It exploits graph centrality measures to expand customized recommendations from the semantic information represented in the graph. The graph shows and chooses graph algorithms for computing chart centrality that is the center of the mobile recommender system are exhibited. Semantic ideas, for example, semantic transcendence and likeness measures, are adjusted to the graph model. Usage challenges confronted to settle execution issues are additionally examined.